Knowledge on National Free Health Services among Preclinical Medical Students - Upadhyay, Hari Prasad; Prasai, Neeti; Prasai, Meera; Sedai, Prativa; Panthi, Sirjana (Journal of College of Medical Sciences-Nepal, 2019)
Background: National free health services are those facilities which are given by the government in free of cost for all the citizens in specific countries. Free health service program provides essential health care services free of charge to all users at Primary Health Care Centers, Health Posts. Methods: A cross-sectional analytical study was conducted among 395 preclinical medical students Bharatpur, Chitwan, Nepal by using non probability sampling technique. In the Bivariate analysis, Chi-square test was done. Before the binary logistic regression Multicollinearity of independent variables was check by using Variance inflation factor (VIF). Binary logistic regression was performed to examine the net effect of each independent variable on the Dependent variable. Results: Result showed that 24.8% students had good knowledge on national free health services (with 95% CI 20.81% to 29.3%). The overall level of knowledge of BPH students had good followed by nursing students. Students who were in the age group 20-25 years had 3.54 times (with 95% CI for OR = 1.869 to 6.689) as compared 15-20 years and students of age 25-30 years had 14.04 times (with 95% CI for OR = 5.292 to 37.262) good knowledge as compare to those who were in the age group 15-20 years. Female students had 2 times (with 95% CI for OR = 1.002 to 3.977) good knowledge as compare to male students. Students who were from BDS had 0.83 times (with 95% CI for OR = 0.159 to 4.319), students who were from Nursing had 1.70 times (with 95% CI for OR = 0.658 to 4.402), students who were from BPH had 4.34 times (with 95% CI for OR = 1.698 to 11.087) and students who were from B Pharmacy had 1.10 times (with 95% CI for OR = 0.415 to 2.941) times higher odds of knowledge as compare to those students who were from MBBS. Conclusions: The overall level of knowledge among the preclinical medical students is poor; only one fourth students had good level of knowledge. Majority of the students don’t know name of the basic free health services provided by government of Nepal. Students of younger adult had good knowledge. BHP and Nursing students had good knowledge as compared to other level. Statistically significant variable with level of knowledge are age (p-value <0.001), gender (p-value 0.049), level of education (p-value<0.001).